Communicative Language Teaching in the Curriculum 2013 - Kalayo Hasibuan (English Instruction, 2020)
Communicative Language Teaching (CLT) plays its role in the implementation of a foreign language instruction in the curriculum of 2013.  CLT implementation will direct English language teachers how to teach English based on the functions of language as communication. In this paper, it will be defined what CLT is, and what are its characteristics and principles of CLT. Then, it will show the relationship between CLT with Curriculum 2013 and the CLT classroom activities.